Queerness, Sex Work, and Refugee Status in Nairobi: A conversation with Queer Sex Workers Initiative for Refugees - Wijesiriwardena, Subha (Anti-Trafficking Review, 2022)
In this interview, the author speaks with Queer Sex Workers Initiative for Refugees: a Nairobi-based grassroots service-provision and advocacy group formed by queer refugees in Kenya who are engaged in sex work. The interview explores the question of how queer identity experiences interact with the policing of borders, labour issues, and refugee status. It teases out the ramifications of the compounding factors of migration and criminalisation of sex work and gender diversity, across borders, to show how these produce discrimination, loss of livelihood, and vulnerability to violence.